Strategies For Optimising The Role Of Youth In Kebumen In Facing The Industrial Revolution 5.0 - Pratiwi, Berlin Insan; Khasanah, Nur (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims, first, to examine the role of Kebumen youth in efforts to revive the local economy. The steps or actions referred to are the efforts of Kebumen youth in utilising technology in the management of their businesses. The second objective of this study is to identify the inhibiting and driving factors that optimise the role of Kebumen youth in the regional economy. The third objective is to develop strategies to optimise the role of Kebumen youth in the economic development process, in this case, the utilisation of technology. This study is an exploratory descriptive study that provides an overview through a series of surveys of selected respondents. This series of surveys was conducted with the aim of describing the phenomena occurring in the community (descriptive function). The results of this study are as follows. MSMEs managed by respondents in Kebumen Regency include businesses in the building materials, foodstuffs, handicrafts, and textiles sectors. The majority of MSME business units in the food sector use simple and makeshift technology (tools). The results of the evaluation and measurement of the TRL of MSMEs in Kebumen show that all samples have passed the measurement at levels 1 to 3. Less than 50% of units have passed the intermediate level measurement, namely levels 4 to 6; while less than 10% of units have passed the upper level measurement, namely levels 7 to 9. This explains that the production aspect of MSMEs in Kebumen requires government intervention in the use of appropriate technology and supporting indicators such as management, hygiene in production, and human resources. The main driving factor in business management carried out by respondents is that managers are sufficiently literate in production technology, although they are not yet fully able to adapt to the ongoing industrial revolution 5.0.